The The Implementation of Spoken Tradition on Positive Character Development in Social Science Learning: - Sitti Maryam (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
Character-based education is a holistic process carried out to develop children’s academic capability and personality through which they eventually adopt wisdom and responsibility. The implementation of spoken tradition in social science learning, to develop students’ positive character, is surely interesting to do. Hence, this study is proposed to describe the effectivities of teaching, students’ learning activities, and the progress of students’ positive character development by implementing spoken tradition in social science learning. This study was used by design a classroom action research which was formally executed through steps covering planning, action, observation, evaluation, and reflection. As many as 36 students were purposively involved as subjects of this study. It was found that by implementing spoken tradition in social science learning, at the end of the cycles, teaching effectivity was improved to 92,70%, students’ learning activities were improved to 86,74%, and their positive character was significantly improved on discipline, honesty, responsibility, care, dan politeness.